Proceedings of the 26th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2020
DOI: 10.1145/3394486.3403251
|View full text |Cite
|
Sign up to set email alerts
|

Deep Exogenous and Endogenous Influence Combination for Social Chatter Intensity Prediction

Abstract: Modeling user engagement dynamics on social media has compelling applications in market trend analysis, user-persona detection, and political discourse mining. Most existing approaches depend heavily on knowledge of the underlying user network. However, a large number of discussions happen on platforms that either lack any reliable social network (news portal, blogs, Buzzfeed) or reveal only partially the inter-user ties (Reddit, Stackoverflow). Many approaches require observing a discussion for some considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…As shown in previous work [7], [8], online topics of discussion are often correlated with different exogenous signals over time. For example, in the context of the Venezuela political crisis, Horawalavithana et al [7] show that Twitter discussions related to the announcement of Juan Guaidó as interim president were dictated by particular external events and news articles reports while Twitter discussions related to Venezuela's former president, Chávez, were strongly correlated with Reddit activity.…”
Section: A Model Designmentioning
confidence: 69%
See 2 more Smart Citations
“…As shown in previous work [7], [8], online topics of discussion are often correlated with different exogenous signals over time. For example, in the context of the Venezuela political crisis, Horawalavithana et al [7] show that Twitter discussions related to the announcement of Juan Guaidó as interim president were dictated by particular external events and news articles reports while Twitter discussions related to Venezuela's former president, Chávez, were strongly correlated with Reddit activity.…”
Section: A Model Designmentioning
confidence: 69%
“…They found news carry different predictive power based on the nature of the entities under study. Dutta et al [8] predict the volume of Reddit discussions in a future short-time horizon leveraging the text from news and initial set of comments using a recurrent neural network architecture. Shrestha et al [19] used a deep learning model to forecast the number of retweets and mentions of a specific news source on Twitter using the network structure observed in the day before the predictions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, we proposed a model which, given a tweet and its hate markers (ratio of hateful tweets and hateful retweets on the user's timeline), along with a set of topical and exogenous signals (news title in this case), predicts which followers of the said user are likely to retweet hateful posts. The motive behind using exogenous signals is to incorporate the influence of external events on a user's posting behaviour [Dutta et al 2020]. Interestingly, we observed that existing information diffusion models that do not consider capturing any historical context of a user or incorporate exogenous signals perform comparably on non-hateful cascades but fail to capture diffusion patterns of hateful users.…”
Section: • Chakraborty and Masudmentioning
confidence: 99%
“…Self-exciting point processes [7,8] were also employed as generative models. Recently, exogenous influence has been incorporated [9,10]. Neural methods, particularly graph embedding-based techniques, are quickly becoming popular [11,12].…”
Section: Introductionmentioning
confidence: 99%